RNA interference (RNAi)-based plasmonic nanomaterials for cancer diagnosis and therapy - Yoon, Jinho; Shin, Minkyu; Lee, Ji-Young; Lee, Sang-Nam; Choi, Jin-Ha; Choi, Jeong-Woo (Journal of controlled release, 2022)
RNA interference (RNAi) is being extensively investigated as a potential therapeutic strategy for cancer treatment. However, RNAi-based therapeutics have not yet been used to treat cancer because of their instability and the difficulty of microRNA (miRNA) delivery. Plasmonic nanoparticle-based RNAi nanotherapeutics have been developed for accurate and sensitive diagnosis and a strong therapeutic effect on cancers by leveraging their ease-of-use and specific properties such as photothermal conversion. In this review, recent strategies and advances in plasmonic nanoparticle-based miRNA delivery are briefly presented to facilitate the detection and treatment of several cancers. The challenges and potential opportunities afforded by the RNAi-based theragnosis field are discussed. We expect that the RNAi-integrated plasmonic nanotherapeutics discussed in this review can provide insights for the early diagnosis and effective treatment of cancer. RNA interference (RNAi) is a potential strategy for cancer diagnosis and treatment. Especially, plasmonic nanomaterial-based RNAi delivery systems have various advantages using its plasmonic property, such as optical imaging and photothermal effect. In this review, recently announced microRNA detection using plasmonic nanomaterials and small interfering RNA (siRNA)-based treatment techniques are briefly described for cancer therapy. [Display omitted]